2021
DOI: 10.3389/fpls.2021.690363
|View full text |Cite
|
Sign up to set email alerts
|

Role of Auxin and Nitrate Signaling in the Development of Root System Architecture

Abstract: The plant root is an important storage organ that stores indole-3-acetic acid (IAA) from the apical meristem, as well as nitrogen, which is obtained from the external environment. IAA and nitrogen act as signaling molecules that promote root growth to obtain further resources. Fluctuations in the distribution of nitrogen in the soil environment induce plants to develop a set of strategies that effectively improve nitrogen use efficiency. Auxin integrates the information regarding the nitrate status inside and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 171 publications
1
19
0
Order By: Relevance
“…As a consequence, it stops the growth of lateral roots within a soil zone poor in nitrates. At the same time, the induced systematic signal released by the apex of the primary root results in a compensatory growth of lateral roots in soil zones rich in nitrates [ 83 ]. The application of N f by the farmer during the growing season leads to the formation of soil zones— foraging patches for a plant, which temporarily differ in the concentration of NO 3 -N. Therefore, it can be concluded that a split N fertilization system is a useful way to increase the efficiency of the applied N f .…”
Section: Factors Affecting Nutrient Uptakementioning
confidence: 99%
“…As a consequence, it stops the growth of lateral roots within a soil zone poor in nitrates. At the same time, the induced systematic signal released by the apex of the primary root results in a compensatory growth of lateral roots in soil zones rich in nitrates [ 83 ]. The application of N f by the farmer during the growing season leads to the formation of soil zones— foraging patches for a plant, which temporarily differ in the concentration of NO 3 -N. Therefore, it can be concluded that a split N fertilization system is a useful way to increase the efficiency of the applied N f .…”
Section: Factors Affecting Nutrient Uptakementioning
confidence: 99%
“…RSA is profoundly affected by a complex regulatory network of hormonal and nitrate signaling pathways. Several studies have shown that nitrate acts as both local signal and systemic signal to regulate biosynthesis, degradation, transport, and signaling of different phytohormones to adjust root system modification ( Vidal et al., 2010 ; Ristova et al., 2016 ; Vega et al., 2019 ; Hu et al., 2021 ). Recently, connections between nitrate responses and Brassinosteriod have been proposed by Genome Wide Association Studies using the Arabidopsis thaliana accessions.…”
Section: Discussionmentioning
confidence: 99%
“…External nitrate has a dural effect on lateral root (LR) growth in Arabidopsis . When exposed to high external nitrate concentrations (> 5 mM), lateral root can be developed in nitrate-rich patches but its outgrowth is inhibited by a systemic signal, which is regulated by miR167/ARF8 and miR393/AFB3-mediated auxin signaling ( Gifford et al., 2008 ; Vidal et al., 2010 ; Hu et al., 2021 ). Besides this systemic inhibitory effect, both emergence and elongation of lateral root is promoted by mild nitrate deficiency, which is commonly described as nitrogen foraging response ( Linkohr et al., 2002 ; Gruber et al., 2013 ; Liu et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sinha et al (2020) documented genetic variation in wheat RSA traits and association with high-and low-affinity nitrate transport systems under optimum and limited N. The roles of nitrate and amino acid regulation of shoot branching, flowering, and panicle development, as well as cell division and expansion in shaping of plant architecture have been demonstrated in cereals (Luo et al, 2020). In plants, N regulation of root branching (Walch-Liu et al, 2006) and the process of nitrate-and auxin-mediated regulation of root structure have been unveiled recently (Hu et al, 2021).…”
Section: Multi-disciplinary Approaches To Investigate Root Traitsmentioning
confidence: 99%